Fermenting Futures: an artistic view on yeast biotechnology. Issue 5 (21st July 2021) - Dumitriu, Anna; May, Alex; Ata, Özge; Mattanovich, Diethard
ABSTRACT: BioArt is a new discipline where artists employ materials and techniques of modern life sciences and create novel meanings of biology, often involving living organisms such as tissue culture, bacteria and yeasts, which may also be genetically engineered. The authors have engaged in a collaboration to develop 'Fermenting Futures', a project designed to explore the significance of yeast for early human history by enabling baking and brewing, all the way to industrial biotechnology and synthetic biology with their potential contributions to fight the climate change. Research in two of the authors' lab provides the materials and thematic lines for the artists to develop their installations. The two main pieces reflect on fermentation as a metabolic trait of baker's yeast and its enormous transformational power for human society, and on the application of synthetic biology to enable yeast to grow and produce materials from carbon dioxide. The role of BioArt to support public engagement and science dissemination is discussed, highlighting the importance of collaborations of scientists and artists on equal terms, as showcased here. Abstract : Fermenting Futures is a BioArt project exploring the significance of yeast biotechnology from a cultural perspective, seeking to engage arts audiences and the general public in the history and future of yeast science and technology.